2011
DOI: 10.1007/s00198-011-1555-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the adherence evaluation of osteoporosis treatment (ADEOS) questionnaire for osteoporotic post-menopausal women

Abstract: SummaryWe developed and validated a specific 12-item questionnaire to evaluate adherence to oral antiresorptive medication by post-menopausal osteoporotic women in everyday practice. Over the following 9 months, an index of ≤16 was associated with an increase in the risk of treatment discontinuation of 1.69 and of 2.10 for new patients who had started treatment within the previous year.IntroductionAdherence to medication in osteoporosis is poor. The goal of this study was to develop and validate a disease-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Among all experienced users (with and without GI symptoms), only 49.2 % had an ADEOS score ≥20, which is indicative of a high probability of medication persistence. Although ADEOS scores were not well correlated with adherence as measured by medication possession ratio (MPR) in the validation study [ 30 ], our results are within the range of adherence to osteoporosis therapy observed in administrative claims studies that calculated adherence as MPR. An MPR threshold of 0.80 is commonly used to distinguish between adherence and non-adherence; in the first year of therapy, typically 34–55 % of patients are adherent to pharmacological osteoporosis treatments [ 8 10 ].…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Among all experienced users (with and without GI symptoms), only 49.2 % had an ADEOS score ≥20, which is indicative of a high probability of medication persistence. Although ADEOS scores were not well correlated with adherence as measured by medication possession ratio (MPR) in the validation study [ 30 ], our results are within the range of adherence to osteoporosis therapy observed in administrative claims studies that calculated adherence as MPR. An MPR threshold of 0.80 is commonly used to distinguish between adherence and non-adherence; in the first year of therapy, typically 34–55 % of patients are adherent to pharmacological osteoporosis treatments [ 8 10 ].…”
Section: Discussionsupporting
confidence: 40%
“…Patients completed four instruments to assess treatment adherence, treatment satisfaction, and HRQoL. Adherence was assessed among experienced users with the 12-item adherence evaluation of osteoporosis (ADEOS) treatment questionnaire, which has been validated in women with osteoporosis [ 30 ]. Scores range from 0 to 22 with scores ≥20 predicative of a high probability of medication persistence.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have pointed out that detailed explanation to the patient about the fracture prevention effects, possible adverse drug reactions, and safety of BP therapy is more important than dosing interval in terms of ensuring persistence [ 21 24 ]. Persistence of BP therapy should be improved not only through prolonging the dosing interval but through individualizing the treatment to meet the patient’s preference and circumstance and thereby motivate him/her to continue treatment [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported health care resource use was categorized as hospitalizations, fractures, surgeries, or visits to a general practitioner, specialist, or emergency department in the preceding 3–6 months. Medication adherence was measured by the Adherence Evaluation of Osteoporosis treatment (ADEOS) questionnaire (Breuil et al, 2012), and treatment satisfaction by the Osteoporosis Patient Satisfaction Questionnaire (OPSAT-Q) (Flood et al, 2006). Untreated participants did not complete the ADEOS or OPSAT-Q questionnaires.…”
Section: Methodsmentioning
confidence: 99%